Ultrasound B-Scan for Posterior Segment and Extraocular Evaluation in Ocular Cysticercosis - Bhatt VD; Bhatt KD; Bhatt DC; Dabir S; Sheth JU; Berendschot TTJM; Erckens RJ; Webers CAB (Clinical Ophthalmology)
Vaidehi D Bhatt,1 Kalpana D Bhatt,1 Deepak C Bhatt,1 Supriya Dabir,2 Jay U Sheth,3 Tos TJM Berendschot,4 Roel J Erckens,4 Carroll AB Webers4 1UBM Institute, Mumbai, India; 2Department of Retina, Rajan Eye Care Pvt Ltd, Chennai, India; 3Department of Retina Services, Shantilal Shanghvi Eye Institute, Mumbai, India; 4University Eye Clinic Maastricht, Maastricht, The NetherlandsCorrespondence: Vaidehi D Bhatt, UBM Institute, A/1 Ganesh Baug, Dadar, Mumbai, 400019, India, Tel +91-9821525810, Email vaidehibhatt94@gmail.comPurpose: Cysticercosis, caused by Taenia solium larvae, can affect various ocular and extraocular structures, leading to significant morbidity. Ultrasound B-scan imaging plays a pivotal role in diagnosing and classifying cysticercosis lesions. The aim of the study was to describe the ultrasound B-scan characteristics of ocular and extraocular cysticercosis, proposing a classification system based on anatomical localization to enhance understanding and management.Patients and Methods: A retrospective study of consecutive cases with intraocular or extraocular cysticercosis was conducted from January 1993 to December 2023 in Mumbai, India. B-scan ultrasound was performed by an experienced imaging specialist. Descriptive statistics were used to summarize demographic characteristics and the proportion of cysticercosis in each anatomical location. Cysticercosis lesions were classified based on anatomical location observed during imaging.Results: Amongst the 56 eyes evaluated, intraocular posterior segment involvement (n=25) and extraocular involvement (n=31) were observed. Extraocular cysticercosis predominantly affected the medial rectus muscle (40%), followed by the inferior rectus (28%), lateral rectus (20%), and superior rectus muscles (12%). Orbital cysts were localized in the posterior extraconal (50%), anterior extraconal (34.33%), and intraconal (16.67%) regions. Intra-vitreous cysticercosis (n=9) exhibited thin-walled cysts with minimal inflammation, progressing to thickened cyst walls in the late stages. Sub-hyaloid cysticercosis (n=8) showed initial thin vitreous detachment, progressing to thickened vitreous adhesions. Sub-retinal cysticercosis (n=9) without retinal detachment indicated early disease, while cases with detachment suggested disease progression.Conclusion: The proposed anatomical classification system based on B-scan ultrasound features provides a structured approach to categorizing cysticercosis lesions, enhancing understanding and management in ophthalmic practice.Keywords: cysticercosis, ultrasound, orbit, vitreous, retina